The Effect of the Modified Reciprocal Teaching Strategy on EFL 5th Year Preparatory School Students’ Achievement in Reading Comprehension - Majeed, Nahida T.; Ahmed, Fatima Shihab (Journal of Tikrit University for Humanities, 2022)
The Modified Reciprocal (MR) teaching strategy is an instructional method, which employs four activities in the form of a dialogue between the teacher and his students with four specific reading strategies that are utilized to assist comprehension, they are: predicting, questioning, clarifying, and summarizing. The current study aims at finding out the effect of the MR teaching strategy on EFL students’ achievement in reading comprehension (RC), through: 1. specifying in detail the MR teaching strategy for teaching English RC 2. finding the average level of students’ performance in English RC 3. finding whether there is any significant difference between the performance of the two groups in the achievement test, on one hand, and 4. between the recognition level and the production level of the achievement test. These aims have been achieved through verifying three null hypotheses. A sample of sixty female preparatory school students that represents 68.96 of its original population has been selected (from the 5th class of Al-Baidah Preparatory School for Girls, in the City of Kirkuk), equalized in a number of variables and divided randomly into two equal experimental and control groups. The two groups have been taught the same instructional material, English for Iraq 5th Preparatory, by using the MR strategy for the experimental group and the conventional method for the control group, for a period of twelve weeks. An achievement test has been constructed, validated, its reliability obtained, its items analyzed, and then applied to the two involved groups of students at the end of the instructional period. The required data is collected and statistically analyzed. The obtained results are as follows: The average level of the EFL 5th year preparatory school students’ performance is within the theoretical mean scores of achievement in RC. There is a significant difference between the mean scores of the two groups’ performance in the achievement test, and in favour of the experimental group. There is a significant difference between the mean scores of the students’ performance at the recognition level and that at the production level, and in favour of the production level. Finally, the study ends up with a number of conclusions and recommendations, as follows